2019
DOI: 10.11646/phytotaxa.391.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic novelties, new records, and rare species of desmids from the Chapada Diamantina region, Brazil

Abstract: We report here taxonomic novelties and interesting records of desmids, including new taxa, rare species and new occurrences, collected at three areas (Piatã, Rio de Contas and Palmeiras) in the Chapada Diamantina region, northeastern Brazil. We identified 16 desmids, including six taxa new to science (Cosmarium diamantinum, Euastrum bicudoi, E. piataense, Micrasterias jenneri var. semicirculare, M. torreyi var. pseudocurvata, and Tetmemorus furcatus), as well as new records for Brazil (Euastrum subcyclopicum v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Little is known on the current known diversity and distribution of that algal group in that northeastern Brazil's semiarid biome. Based only on taxonomic and floristic studies (Förster 1964;Ramos et al 2019;2020), there are only 13 taxa of Cosmarium reported to that domain (12 from Bahia and only one in Piaui), including some endemic taxa such as Cosmarium decedens var. bahiense, C. diamantinum, C. femmeasense, and C. subundulatum var.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known on the current known diversity and distribution of that algal group in that northeastern Brazil's semiarid biome. Based only on taxonomic and floristic studies (Förster 1964;Ramos et al 2019;2020), there are only 13 taxa of Cosmarium reported to that domain (12 from Bahia and only one in Piaui), including some endemic taxa such as Cosmarium decedens var. bahiense, C. diamantinum, C. femmeasense, and C. subundulatum var.…”
Section: Introductionmentioning
confidence: 99%